Penerapan VIKOR Dalam Pemilihan Calon Ketua DPC Peradi Vikor - Atika Suri; Nelly Astuti Hasibuan; Fadlina Fadlina (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
The Indonesian Advocates Association (PERADI) is an advocate organization referred to in law number 18 of 2003 (